Legal Regulation on Nuclear-Powered Ships Activity in Indonesian Waters Territory - Elieser Ginting; Pujo Widodo; Bayu Setiawan (CV. Rayyan Dwi Bharata, 2023)
On 17 September 2021, Australia, the United Kingdom and the United States signed the AUKUS agreement legitimizing the ownership and development of Australian nuclear-powered submarines. This has direct implications for Indonesia, which has a strategic position as a trade route. In response to this, Indonesia has taken several political steps at the regional level as well as in multilateral forums. This research is intended to analyze legal steps that can be taken by Indonesia to regulate the navigation and safety of nuclear-powered submarines considering that international maritime law instruments do not accommodate these concerns. Through a normative legal approach, using the theory of Critical Legal Studies and the Concept of Legal Politics, this research finds that Indonesia needs to regulate provisions for the navigation and safety of nuclear-powered submarines at the national level.